Payanie Swamp Ecotourism Landscape as a Tourism Object Destination in Bireuen District, Aceh Province - Murni, Sri; Rahmi Novalita, Rahmi Novalita; Iqbal, Muhammad (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to describe the Payanie swamp ecotourism landscape as a natural tourism destination. This type of research is qualitative research. The research was conducted in Payanie swamp ecotourism, Bireuen Regency, Aceh Province. This research uses data sources in the form of an inventory and tourism approach, and uses key informants, namely the manager of the Payanie swamp tourist attraction. Data analysis techniques use data reduction, data display, data interpretation, and drawing conclusions. The research results show that; 1) the Payanie swamp ecotourism landscape as a tourist destination is the Payanie swamp including; Payanie swamp land, Payanie swamp animals and Payanie swamp plants, 2) management of Payanie swamp ecotourism is managed well by the private sector, namely the Aceh Wethland Foundation (AWF) and in collaboration with PT. Iskandar Muda Fertilizer.